English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

if f(x) = 4x + 2, and g(x) = -2x - 1 then what is

2f(-1/4) - 3g(4)?

2007-09-15 07:01:13 · 3 answers · asked by San Fran Kid 2 in Science & Mathematics Mathematics

3 answers

if f(x) = 4x+2, and g(x) = -2x - 1 then what is 2f(-1/4) - 3g(4)?
2f(-1/4) = 2(4(-1/4) +2 = 2
3g(4) = 3(-2(4) -1)= -27
So 2f(-1/4) - 3g(4) = 2 -(-27) = 29

2007-09-15 07:10:07 · answer #1 · answered by ironduke8159 7 · 0 0

2[4(-1/4)+2] - 3[-2(4)-1]

2[(-4/4)+2] - 3[-8-1]

2[-1+2] - 3[-9]

2(1) + 27

= 29

2007-09-15 14:19:10 · answer #2 · answered by one 1 · 0 0

plug -1/4 into f(x) then multiply by 2
plug 4 in g(x) then multiply by -3
add the two numbers

2007-09-15 14:11:15 · answer #3 · answered by CT 3 · 0 0

fedest.com, questions and answers